Induction of Settlement in Larvae of the Mussel Mytilus Galloprovincialis Using Neuroactive Compounds - Young, T; Sánchez-Lazo, C; Martínez-Pita, I; Alfaro, AC (Elsevier, 2012)
We investigated the effect on Mytilus galloprovincialis larval settlement, as well as the toxicity, of serial concentrations in filtered seawater of acetylcholine (AC), γ-aminobutiric acid (GABA); 3-isobutyl-1-methylxanthine (IBMX); and the potassium ion in the form of potassium chloride (KCl) and potassium sulfate (K2SO4). All the substances assayed induced larval settlement and peak responses were above 90% in exposures to 10− 2 mol L− 1 (M) AC, 10− 4 and 10− 5 M epinephrine, 10− 3 M GABA and 20, 30 and 40 mM KCl. The optimal concentration of K+ varied depending on the anionic component of the compound assayed, and peak settlement response to KCl was higher (100%) than that achieved with K2SO4 (69.7%). The estimated LC50 of the compounds assayed ranged from 9.4 × 10− 6 M (GABA) to 3.1 × 10− 2 M (KCl). GABA, IBMX and K2SO4 treatments displayed toxic effects in all the active concentrations. In contrast, AC 10− 5 M, epinephrine 10− 4 and 10− 5 M and KCl 20 mM treatments enhanced larval settlement without an acute short-term effect on mortality. These results provide new insights on the molecular mechanisms controlling settlement in M. galloprovincialis larvae, and yield promising outcomes for the mussel industry to find a reliable method to enhance larval settlement in hatcheries.
Keywords: Mediterranean mussel; Potassium